New Directions in Telecollaborative Research and Practice: Selected Papers From the Second Conference on Telecollaboration in H 2016
DOI: 10.14705/rpnet.2016.telecollab2016.502
|View full text |Cite
|
Sign up to set email alerts
|

Interactional dimension of online asynchronous exchange in an asymmetric telecollaboration

Abstract: T he telecollaborative project under study involves, on the one hand, Masters students who are studying to become teachers and who design the tasks as well as tutor them, and, on the other hand, French language students. The relationship in this type of telecollaboration has been shown to be both asymmetric and symmetric. The hypothesis this paper seeks to examine is that designing tasks and providing corrective feedback by the 'native' partners tends to take precedence over less formal exchanges. We thus anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hall & Walsh, 2002;Heritage, 2005;Seedhouse, 2009). In telecollaboration studies where interaction patterns have been explored (Liddicoat & Tudini, 2013;Loizidou & Mangenot, 2016), similar findings have been made, only it is usually the 'native speaker' student who takes on the 'teacher/tutor' identity by providing feedback on the 'non-native' peer's 'errors'. A recent study by Dooly and Tudini (2016) on the other hand found that in a dyadic pair of studentteachers, the non-native peer took on the role of teacher/tutor more frequently than the native speaker, in regards to 'guiding' the online talk.…”
Section: The Positionality Principlementioning
confidence: 85%
“…Hall & Walsh, 2002;Heritage, 2005;Seedhouse, 2009). In telecollaboration studies where interaction patterns have been explored (Liddicoat & Tudini, 2013;Loizidou & Mangenot, 2016), similar findings have been made, only it is usually the 'native speaker' student who takes on the 'teacher/tutor' identity by providing feedback on the 'non-native' peer's 'errors'. A recent study by Dooly and Tudini (2016) on the other hand found that in a dyadic pair of studentteachers, the non-native peer took on the role of teacher/tutor more frequently than the native speaker, in regards to 'guiding' the online talk.…”
Section: The Positionality Principlementioning
confidence: 85%